A cross-sectional study on COVID19 mortality among people below 30 years of age in Tamilnadu-2020 - V. Vijay Anand; G. Arunkumar Yogaraj; S. Priya; P. Priya Raj; C. Brinda Priyadharshini; P.N. Sridevi (Elsevier, 2021)
Introduction: The COVID19 pandemic has turned out to be one of the public health* burdens in 2020. The fear of deaths due to COVID19 has surmounted even in developed countries and hasn't spared young age. This study aims in assessing the mortality due to COVID19 among patients below 30years of age in TamilNadu. Methods: The data was collected from a publicly available secondary data source(www.stopcorona.tn.gov.in)which is an official COVID19 state dashboard. Details of the young COVID19 deaths* under 30yrs of age, their gender, symptoms, Co-morbidities, date of symptoms, date of admission, and death were collected till October 2020. A total of 158 deaths were included in the analysis. Fischer exact test and Mann Whitney U test* were used and p-value <0.05 was considered significant. Results: Among the 158 COVID19 deaths under 30 years of age, the median age affected was 25 years(IQR-7) and 70.3% (n-111) had at least one co-morbidity*. The median time interval between symptom onset and hospital admission was 3 days (IQR-3) and between admission and death was 4 days(IQR-7).There was a significant association of myocarditis, refractory seizures, Central nervous system involvement as the cause of death in the age group 0-15years, compared with 16-30years(p < 0.05). The majority of deaths occurred with a late presentation, also patients with higher age were admitted after 2 days of symptoms and the results were statistically significant(p < 0.05). Conclusion: Understanding the age-dependent risk gradient and their trend of this new virus at young age* is essential for public health planning and prevent future deaths, future research gateways.